Productive disasters? Evidence from European firm level data - Andrea M. Leiter; Harald Oberhofer; Paul A. Raschky (University of Innsbruck, Department of Public Finance, 2007)
This paper examines the impact of floods on firms' capital accumulation, employment growth and productivity by using a difference-in-difference approach and considering firms' asset structure. We find evidence that companies in flooding regions show higher growth of total assets and employment than firms in areas which did not face a flooding. This positive effect is even more pronounced for companies with larger shares of intangible assets. Regarding the firms' productivity a significantly negative flood effect is observable which declines with increasing share of intangible assets.
Keywords: D24; Q54; R10; C21; 330; natural disasters; firm growth; Gibrat's Law; productivity; difference-in-differences; Überschwemmung; Produktivität; Unternehmenswachstum; Schätzung; Europa